Method for preparing automobile brake disc
In the preparation of automobile brake discs, ceramic particles are used to enhance the different volume content and forming process of aluminum-based composite materials, the problem of mutual penetration of materials is solved, and the consistency of material distribution and interface combination strength are improved to meet the performance needs of brake discs.
Patent Information
- Application Number
- CN202310749122.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-25
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-06-25
AI Technical Summary
In traditional powder metallurgy technology, ceramic particle-reinforced aluminum-based composite materials are prone to penetrate each other during powder filling and pressing forming, making it difficult to ensure the consistency of material distribution, affecting the interface strength and the application of brake discs.
By providing the first ceramic particle-reinforced aluminum-based composite material and the second ceramic particle-reinforced aluminum-based composite material, and pre-pressing and combined forming are performed in the forming mold, the pre-pressing pressure is defined to be 5% to 20% of the combined pressure, so as to avoid interpenetration of materials and ensure consistency of material distribution and interface bonding strength.
The appearance and strength of the automobile brake disc are achieved intact and suitable. The interface of the disc cap and disc body are intact and crack-free, which improves the consistency of material distribution and interface strength to meet the performance needs of the brake disc.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of powder metallurgy, in particular to a method for preparing an automobile brake disc. Background Art
[0002] Lightweighting is one of the most effective means to achieve energy conservation and consumption reduction for automobiles and other transportation vehicles. Using high-performance light metal materials instead of steel materials in key moving parts such as engines and brake discs of transportation equipment can not only reduce the weight of the entire vehicle and reduce the momentum of high-speed moving parts of transportation equipment, but also significantly improve the dynamic performance of transportation equipment while reducing energy consumption.
[0003] Ceramic-reinforced aluminum-based composite materials have low density, high specific strength and specific stiffness, high thermal conductivity, and excellent wear resistance, abrasion resistance, and corrosion resistance, and have broad application prospects in the field of lightweight structural parts. Specifically applied to brake discs, since the disc body needs to have high temperature resistance, wear resistance and other properties, and the disc cap needs to have relatively high mechanical properties, the disc body usually uses a high volume fraction of ceramic-reinforced aluminum-based composite materials, and the disc cap usually uses a low volume fraction of ceramic-reinforced aluminum-based composite materials to meet their respective performance requirements. However, when the above-mentioned brake discs are prepared using traditional powder metallurgy processes, the two powder materials are prone to mutual penetration during the powder filling and pressing process, making it difficult to ensure the consistency of the distribution of the two materials, affecting the interface strength between the materials and limiting their application. Summary of the invention
[0004] Based on this, it is necessary to provide a method for preparing an automobile brake disc which can effectively avoid the mutual penetration of two powder materials, ensure the distribution consistency of the two materials, and have a complete interface and no cracks.
[0005] A method for preparing an automobile brake disc comprises the following steps:
[0006] A first ceramic particle reinforced aluminum-based composite material and a second ceramic particle reinforced aluminum-based composite material are provided, wherein the volume content of ceramic particles in the first ceramic particle reinforced aluminum-based composite material is 20% to 30%, the volume content of ceramic particles in the second ceramic particle reinforced aluminum-based composite material is 30% to 50%, and the volume content of ceramic particles in the first ceramic particle reinforced aluminum-based composite material and the second ceramic particle reinforced aluminum-based composite material are not both 30%;
[0007] Providing a forming mold, the forming mold having a disc body cavity and a disc cap cavity;
[0008] After the second ceramic particle reinforced aluminum-based composite material is placed in the cavity of the disc body for pre-pressing, the first ceramic particle reinforced aluminum-based composite material is placed in the cavity of the disc cap, and pressed together to obtain a green body, wherein the pre-pressing pressure is 5% to 20% of the pressing pressure;
[0009] The green compact is sintered and shaped in sequence to obtain the automobile brake disc.
[0010] In one embodiment, when the volume content of ceramic particles in the second ceramic particle reinforced aluminum-based composite material is less than 35%, the pre-pressing pressure is 5% to 10% of the combined pressing pressure; when the volume content of ceramic particles in the second ceramic particle reinforced aluminum-based composite material is 35% to 45%, the pre-pressing pressure is 10% to 15% of the combined pressing pressure; when the volume content of ceramic particles in the second ceramic particle reinforced aluminum-based composite material is greater than 45%, the pre-pressing pressure is 15% to 20% of the combined pressing pressure.
[0011] In one embodiment, the powder filling height H1 of the first ceramic particle reinforced aluminum-based composite material in the disk cap cavity satisfies the following conditions:
[0012] H1=[(a / b)×H2]~[(a / b)×H2+3mm],
[0013] Wherein, a is the powder compression ratio of the first ceramic particle reinforced aluminum matrix composite material under combined pressing conditions;
[0014] b is the powder compression ratio of the second ceramic particle reinforced aluminum matrix composite material under combined pressing conditions;
[0015] H2 is the powder filling height of the second ceramic particle reinforced aluminum-based composite material in the disc cavity, in mm.
[0016] In one of the embodiments, the powder filling height H2 of the second ceramic particle reinforced aluminum-based composite material in the disc cavity is 45 mm to 90 mm.
[0017] In one embodiment, the powder compression ratio a of the first ceramic particle reinforced aluminum-based composite material under combined pressing conditions is 1.8 to 2.5; the powder compression ratio b of the second ceramic particle reinforced aluminum-based composite material under combined pressing conditions is 1.8 to 2.5;
[0018] In one embodiment, the combined pressing pressure is 150 MPa to 300 MPa.
[0019] In one embodiment, the sintering is carried out in stages. The sintering temperature of the first stage is 300°C to 400°C, and the sintering time is 30min to 60min. The sintering temperature of the second stage is 580°C to 630°C, and the sintering time is 90min to 150min.
[0020] In one embodiment, the sintering is performed in a protective gas atmosphere, and the protective gas is nitrogen or argon.
[0021] In one embodiment, the sintering shrinkage of the first ceramic particle reinforced aluminum-based composite material in the second stage is 1.8% to 2.6%; the sintering shrinkage of the second ceramic particle reinforced aluminum-based composite material in the second stage is 3.0% to 4.2%.
[0022] In one embodiment, the forming mold includes an inner ring pressing mold group, an outer ring pressing mold group and a female mold. The inner ring pressing mold is assembled to form the disc cap cavity within the outer ring pressing mold group, and the outer ring pressing mold is assembled to form the disc body cavity between the female mold and the inner ring pressing mold group.
[0023] The preparation method of the above-mentioned automobile brake disc is to place a second ceramic particle reinforced aluminum-based composite material with a ceramic particle volume content of 30% to 50% in the disc body cavity for pre-pressing to obtain a pre-pressed blank, and then place a first ceramic particle reinforced aluminum-based composite material with a ceramic particle volume content of 20% to 30% in the disc cap cavity and press it together with the pre-pressed blank. By limiting the pre-pressing pressure to 5% to 20% of the pressing pressure, a pre-pressed blank with a good appearance and suitable strength can be obtained. On the one hand, the mutual penetration of the two materials can be avoided and the consistency of the distribution of the two materials is ensured. On the other hand, the bonding strength of the blank interface after pressing is ensured. Then, the automobile brake disc is obtained after sintering and shaping, and the interface between the disc cap and the disc body is well bonded and free of cracks. DETAILED DESCRIPTION
[0024] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below, and preferred embodiments of the present invention are provided. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0026] A method for preparing a vehicle brake disc according to an embodiment of the present invention comprises the following steps S110 to S140:
[0027] S110, providing a first ceramic particle reinforced aluminum-based composite material and a second ceramic particle reinforced aluminum-based composite material.
[0028] The volume content of the ceramic particles in the first ceramic particle reinforced aluminum-based composite material is 20% to 30%, and the volume content of the ceramic particles in the second ceramic particle reinforced aluminum-based composite material is 30% to 50%.
[0029] It is particularly important to emphasize that the volume contents of the ceramic particles in the first ceramic particle reinforced aluminum-based composite material and the second ceramic particle reinforced aluminum-based composite material in the present application are not both 30% in order to optimize the performance distribution of the disk cap and the disk body.
[0030] Furthermore, the volume content of the ceramic particles in the first ceramic particle reinforced aluminum-based composite material is 25%, and the volume content of the ceramic particles in the second ceramic particle reinforced aluminum-based composite material is 40%.
[0031] S120. Provide a forming mold, wherein the forming mold has a disc body cavity and a disc cap cavity.
[0032] In this embodiment, the forming mold includes an inner ring pressing mold set, an outer ring pressing mold set and a female mold. The inner ring pressing mold is assembled to enclose the outer ring pressing mold set to form a disc cap cavity, and the outer ring pressing mold is assembled to enclose the female mold set and the inner ring pressing mold set to form a disc body cavity.
[0033] In this embodiment, the shape of the disc body cavity is annular corresponding to the brake disc body, and the shape of the disc cap cavity is annular corresponding to the brake disc disc cap. Therefore, the green body formed by the forming mold is a concentrically arranged inner and outer ring structure, and the corresponding inner ring can be shaped into a disc cap during subsequent shaping, which can greatly improve production efficiency and realize continuous production of aluminum-based composite automotive brake discs.
[0034] S130, after the second ceramic particle reinforced aluminum-based composite material is placed in the cavity of the disc body for pre-pressing, the first ceramic particle reinforced aluminum-based composite material is placed in the cavity of the disc cap, and pressed together to obtain a green body.
[0035] It should be noted that after the first ceramic particle reinforced aluminum-based composite material is laid in the disc cap cavity, its upper surface needs to be flush with the upper surface of the second ceramic particle reinforced aluminum-based composite material pre-pressed blank.
[0036] The pre-pressing pressure is 5% to 20% of the closing pressure. Further, the closing pressure is 150 MPa to 300 MPa.
[0037] It can be understood that if the pre-pressing pressure is too large, the combination of the two materials will be weak after filling and pressing, and cracks will easily appear on the interface after sintering; if the pre-pressing pressure is too small, the strength of the green body after pre-pressing will be weak, and it will be easy to be damaged during the subsequent preparation process.
[0038] Further, when the volume content of the ceramic particles in the second ceramic particle reinforced aluminum-based composite material is less than 35%, the pre-pressing pressure is 5% to 10% of the combined pressure. When the volume content of the ceramic particles in the second ceramic particle reinforced aluminum-based composite material is 35% to 45%, the pre-pressing pressure is 10% to 15% of the combined pressure. When the volume content of the ceramic particles in the second ceramic particle reinforced aluminum-based composite material is greater than 45%, the pre-pressing pressure is 15% to 20% of the combined pressure.
[0039] Since there are differences in powder compression ratio and sintering shrinkage rate of the first ceramic particle reinforced aluminum-based composite material and the second ceramic particle reinforced aluminum-based composite material under the same conditions, in order to make the upper and lower surfaces of the inner and outer rings uniform after sintering, it is necessary to control the powder filling height of the inner and outer rings, that is, the powder filling height of the first ceramic particle reinforced aluminum-based composite material in the disk cap cavity and the powder filling height of the second ceramic particle reinforced aluminum-based composite material in the disk body cavity.
[0040] In this embodiment, the powder filling height H1 of the first ceramic particle reinforced aluminum-based composite material in the disk cap cavity needs to meet the following conditions:
[0041] H1=[(a / b)×H2]~[(a / b)×H2+3mm],
[0042] Wherein, a is the powder compression ratio of the first ceramic particle reinforced aluminum matrix composite material under combined pressing conditions;
[0043] b is the powder compression ratio of the second ceramic particle reinforced aluminum matrix composite material under combined pressing conditions;
[0044] H2 is the powder filling height of the second ceramic particle reinforced aluminum-based composite material in the disc cavity, in mm.
[0045] Furthermore, the powder compression ratio of the first ceramic particle reinforced aluminum matrix composite material under the combined pressing condition is 1.8 to 2.5. The powder compression ratio of the second ceramic particle reinforced aluminum matrix composite material under the combined pressing condition is 1.8 to 2.5.
[0046] Furthermore, the powder filling height H2 of the second ceramic particle reinforced aluminum-based composite material in the disc cavity is 45 mm to 90 mm.
[0047] S140, sintering and shaping the green compact in sequence to obtain a brake disc for an automobile.
[0048] In this embodiment, sintering is performed in stages. In the first stage, the sintering temperature is 300°C to 400°C and the sintering time is 30min to 60min to remove impurities on the surface of the green body; in the second stage, the sintering temperature is 580°C to 630°C and the sintering time is 90min to 150min to densify the green body.
[0049] Furthermore, the sintering is carried out in a protective gas atmosphere, wherein the protective gas is nitrogen or argon.
[0050] After sintering, the sintered workpiece directly enters the shaping die for die forging. The shaping die temperature is greater than 400°C; the die forging pressure is 150MPa~300MPa.
[0051] The preparation method of the above-mentioned automobile brake disc is to place a second ceramic particle reinforced aluminum-based composite material with a ceramic particle volume content of 30% to 50% in the disc body cavity for pre-pressing to obtain a pre-pressed blank, and then place a first ceramic particle reinforced aluminum-based composite material with a ceramic particle volume content of 20% to 30% in the disc cap cavity and press it together with the pre-pressed blank. By limiting the pre-pressing pressure to 5% to 20% of the pressing pressure, a pre-pressed blank with a good appearance and suitable strength can be obtained. On the one hand, the mutual penetration of the two materials can be avoided and the consistency of the distribution of the two materials is ensured. On the other hand, the bonding strength of the blank interface after pressing is ensured. Then, the automobile brake disc is obtained after sintering and shaping, and the interface between the disc cap and the disc body is well bonded and free of cracks.
[0052] The following are specific embodiments.
[0053] Example 1
[0054] (1) Providing a first ceramic particle reinforced aluminum matrix composite material with a ceramic particle volume content of 20%, whose powder compression ratio at 150 MPa is 2.3, and whose sintering shrinkage at 580°C is 2.12%; providing a second ceramic particle reinforced aluminum matrix composite material with a ceramic particle volume content of 30%, whose powder compression ratio at 150 MPa is 2.1, and whose sintering shrinkage at 580°C is 3.15%.
[0055] (2) A forming mold is provided, wherein the forming mold has a disc body cavity and a disc cap cavity.
[0056] (3) The second ceramic particle reinforced aluminum-based composite material is evenly laid in the disc body cavity with a laying thickness of 45 mm. After pre-pressing at 7.5 MPa, the first ceramic particle reinforced aluminum-based composite material is evenly laid in the disc cap cavity with a laying thickness of 49 mm. After pressing at 150 MPa, a green body is obtained. It is observed that the interface distribution of the inner and outer rings of the green body is consistent, the combination is intact, there is no thickness difference between the inner and outer layers, and the appearance is intact.
[0057] (4) The temperature of the first zone of the continuous sintering furnace is set at 300°C. After the green body is sintered in this zone for 60 minutes, it is pushed into the second zone. The temperature of the second zone is set at 580°C. After the green body is sintered for 150 minutes, the sintered workpiece enters the shaping mold and the disc cap is shaped to obtain the automobile brake disc.
[0058] After testing, the interface bonding strength between the disc cap and the disc body of the automobile brake disc is 172±21MPa. It has completed and passed the T / CAAMTB09-2018 high load and JascC419-2006 torsion destruction bench tests, indicating that the brake disc's structural strength and friction and wear performance meet the requirements of the brake disc.
[0059] Example 2
[0060] (1) Providing a first ceramic particle reinforced aluminum matrix composite material with a ceramic particle volume content of 30%, whose powder compression ratio at 300 MPa is 2.1, and whose sintering shrinkage at 630°C is 2.6%; providing a second ceramic particle reinforced aluminum matrix composite material with a ceramic particle volume content of 50%, whose powder compression ratio at 300 MPa is 1.8, and whose sintering shrinkage at 630°C is 4.2%.
[0061] (2) A forming mold is provided, wherein the forming mold has a disc body cavity and a disc cap cavity.
[0062] (3) The second ceramic particle reinforced aluminum-based composite material is evenly laid in the disc body cavity with a laying thickness of 90 mm. After pre-pressing at 60 MPa, the first ceramic particle reinforced aluminum-based composite material is evenly laid in the disc cap cavity with a laying thickness of 105 mm. After pressing at 300 MPa, a green body is obtained. It is observed that the interface distribution of the inner and outer rings of the green body is consistent, the combination is intact, and the appearance is also intact.
[0063] (4) The temperature of the first zone of the continuous sintering furnace was set at 400 °C. After the green body was sintered in this zone for 30 min, it was pushed into the second zone. The temperature of the second zone was set at 630 °C. After the green body was sintered for 90 min.
[0064] After testing, the interface bonding strength between the disc cap and the disc body of the automobile brake disc is 162±17MPa. It has completed and passed the T / CAAMTB09-2018 high load and JascC419-2006 torsion destruction bench tests, indicating that the brake disc's structural strength and friction and wear performance meet the requirements of the brake disc.
[0065] Example 3
[0066] (1) Providing a first ceramic particle reinforced aluminum matrix composite material with a ceramic particle volume content of 25%, which has a powder compression ratio of 2.4 at 200 MPa and a sintering shrinkage rate of 3.5% at 600°C; providing a second ceramic particle reinforced aluminum matrix composite material with a ceramic particle volume content of 40%, which has a powder compression ratio of 2.0 at 200 MPa and a sintering shrinkage rate of 2.4% at 600°C.
[0067] (2) A forming mold is provided, wherein the forming mold has a disc body cavity and a disc cap cavity.
[0068] (3) The second ceramic particle reinforced aluminum-based composite material is evenly laid in the disc body cavity with a laying thickness of 60 mm. After pre-pressing at 30 MPa, the first ceramic particle reinforced aluminum-based composite material is evenly laid in the disc cap cavity with a laying thickness of 72 mm. After pressing at 200 MPa, a green body is obtained. It is observed that the interface distribution of the inner and outer rings of the green body is consistent, the combination is intact, and the appearance is also intact.
[0069] (4) The green body is sintered at 350°C for 50 min and then sintered at 600°C for 120 min to shape the disc cap, thereby obtaining an automobile brake disc.
[0070] After testing, the interface bonding strength between the disc cap and the disc body of the automobile brake disc is 185MPa. It has completed and passed the T / CAAMTB09-2018 high load and JascC419-2006 torsion destruction bench tests, indicating that the brake disc's structural strength and friction and wear performance meet the requirements of the brake disc.
[0071] Comparative Example 1
[0072] Comparative Example 1 is basically the same as Example 3, except that the pre-pressing pressure in Comparative Example 1 is less than 7.5MPa. It is found that in the subsequent preparation process, the pre-pressed blank is damaged. In the process of laying the first ceramic particle reinforced aluminum-based composite material in the disk cap cavity, the powder material enters the damaged position of the pre-pressed blank. After pressing, the two materials penetrate each other, the shape of the blank interface is irregular, and the first ceramic particle reinforced aluminum-based composite material enters the friction layer, affecting the wear resistance of the disk.
[0073] Comparative Example 2
[0074] Comparative Example 2 is basically the same as Example 3, except that the pre-pressing pressure in Comparative Example 2 is greater than 60 MPa. It is found that since the pre-pressed green body was pressed too tightly, the inner and outer rings were weakly bonded after pressing, and cracks appeared between the inner and outer layers of the material at the interface of the sintered green body.
[0075] Comparative Example 3
[0076] Comparative Example 3 is basically the same as Example 3, except that the powder filling height of the first ceramic particle reinforced aluminum-based composite material in Comparative Example 3 is 78 mm. The results show that after forming, there is a thickness difference between the inner ring and the outer ring, and the difference exceeds 1.8 mm. There is an obvious step at the interface between the upper and lower surfaces of the green body. After sintering, the outer ring shrinks more than the inner ring, and a full circle of cracks appears at the interface of the green body.
[0077] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing an automobile brake disc, characterized in that: The following steps are involved: A first ceramic particle reinforced aluminum-based composite material and a second ceramic particle reinforced aluminum-based composite material are provided, wherein the volume content of ceramic particles in the first ceramic particle reinforced aluminum-based composite material is 20% to 30%, the volume content of ceramic particles in the second ceramic particle reinforced aluminum-based composite material is 30% to 50%, and the volume content of ceramic particles in the first ceramic particle reinforced aluminum-based composite material and the second ceramic particle reinforced aluminum-based composite material are not both 30%; Providing a forming mold, the forming mold having a disc body cavity and a disc cap cavity; After the second ceramic particle reinforced aluminum-based composite material is placed in the cavity of the disc body for pre-pressing, the first ceramic particle reinforced aluminum-based composite material is placed in the cavity of the disc cap, and pressed together to obtain a green body, wherein the pre-pressing pressure is 5% to 20% of the pressing pressure; The green compact is sequentially sintered and shaped to obtain the automobile brake disc; The powder filling height H1 of the first ceramic particle reinforced aluminum-based composite material in the disk cap cavity satisfies the following conditions: H1=[(a / b)×H2]~[(a / b)×H2+3mm], Wherein, a is the powder compression ratio of the first ceramic particle reinforced aluminum matrix composite material under combined pressing conditions; b is the powder compression ratio of the second ceramic particle reinforced aluminum matrix composite material under combined pressing conditions; H2 is the powder filling height of the second ceramic particle reinforced aluminum-based composite material in the disc cavity, in mm; The powder filling height H2 of the second ceramic particle reinforced aluminum-based composite material in the disc cavity is 45 mm to 90 mm; The powder compression ratio a of the first ceramic particle reinforced aluminum-based composite material under combined pressing conditions is 1.8 to 2.5; the powder compression ratio b of the second ceramic particle reinforced aluminum-based composite material under combined pressing conditions is 1.8 to 2.
5.
2. The method for preparing a vehicle brake disc according to claim 1, characterized in that: When the volume content of ceramic particles in the second ceramic particle reinforced aluminum-based composite material is less than 35%, the pre-pressing pressure is 5% to 10% of the combined pressing pressure; when the volume content of ceramic particles in the second ceramic particle reinforced aluminum-based composite material is 35% to 45%, the pre-pressing pressure is 10% to 15% of the combined pressing pressure; when the volume content of ceramic particles in the second ceramic particle reinforced aluminum-based composite material is greater than 45%, the pre-pressing pressure is 15% to 20% of the combined pressing pressure.
3. The method for preparing a vehicle brake disc according to claim 1 or 2, characterized in that: The combined pressing pressure is 150MPa to 300MPa.
4. The method for preparing a vehicle brake disc according to claim 1, characterized in that: The sintering is carried out in stages. The sintering temperature of the first stage is 300° C. to 400° C., and the sintering time is 30 min to 60 min. The sintering temperature of the second stage is 580° C. to 630° C., and the sintering time is 90 min to 150 min.
5. The method for preparing a vehicle brake disc according to claim 1 or 4, characterized in that: The sintering is performed in a protective gas atmosphere, and the protective gas is nitrogen or argon.
6. The method for preparing a vehicle brake disc according to claim 5, characterized in that: The sintering shrinkage rate of the first ceramic particle reinforced aluminum-based composite material in the second stage is 1.8% to 2.6%; the sintering shrinkage rate of the second ceramic particle reinforced aluminum-based composite material in the second stage is 3.0% to 4.2%.
7. The method for preparing a vehicle brake disc according to claim 1, characterized in that: The forming mold includes an inner ring pressing mold group, an outer ring pressing mold group and a female mold. The inner ring pressing mold is assembled to enclose the outer ring pressing mold group to form the disc cap cavity, and the outer ring pressing mold is assembled to enclose the female mold and the inner ring pressing mold group to form the disc body cavity.
Citation Information
Patent Citations
Light-weight automobile brake disc
CN217081206U